Tracking the sources of allochthonous organic matter along a subtropical fluvial-estuarine gradient using molecular proxies in view of land uses. (July 2020) - Cabral, Ana Caroline; Dauner, Ana Lúcia Lindroth; Xavier, Fernanda Caroline Borato; Garcia, Marina Reback Domingues; Wilhelm, Marines Maria; dos Santos, Vanessa Cristina Gonçalves; Netto, Sergio Antônio; Martins, César C.
Abstract: Sedimentary sterols and linear alkylbenzenes associated with allochthonous organic matter (AOM) inputs were studied in surface sediments along the Tubarão riverbed, South Brazil. These markers were analysed in terms of concentrations, diagnostic ratios and by using multivariate analyses to identify the main organic matter sources. It was necessary to integrate all these factors to distinguish the sources and determine sewage contamination. Phytosterols predominated over faecal sterols, but the contributions of livestock waste along the river (determined in 50% of the sites) were confirmed by the fingerprint analysis. Raw sewage contamination was verified at one site, according to the increased levels of sewage molecular markers and confirmed by the multivariate analyses and diagnostic ratios calibrated to this region. A possible synergistic effect between inorganic nanoparticles from coal mine waste and organic contaminants related to AOM input was suggested and should not be ignored since both activities severely contribute to the environmental changes in much of this fluvial-estuarine gradient from the South Atlantic. Graphical abstract: Image 1 Highlights: Sterols and LABs reveal sewage and livestock waste input in river sediments. Livestock waste contributed to coprostanol amount, interfering in sewage assessment. Faecal sources were distinguished by PCA and Cluster analysis. Coal mine waste interferes with the sedimentary deposition of organic markers.